Distance to Market and Search Costs in an African Maize Market - Mahdi, Shireen (World Bank, Washington, DC, 2012)
Farm-gate buying by small itinerant buyers is the dominant mode of primary marketing in Tanzania's maize market. This paper estimates the effect of household distance to market on maize farm-gate prices, and the extent to which seasonally determined search costs can explain price variations between the lean and the harvest seasons using data from the most recent Tanzania Household Budget Survey (2007). The author observes that greater distance to market depresses farm-gate prices but that it is a relatively modest effect, and that this effect is pro-cyclical in that it is stronger during the harvest season when prices are lowest. The paper discusses the latter result with reference to search costs as an explanatory factor. It also briefly places the findings in the context of Tanzania's food security patterns, making a link between food insecurity and high search costs. The main policy conclusion is that coordinating mechanisms such as village market places (in parallel with farm-gate buying) may reduce transaction costs in rural markets.